Choan-Seng Song's theology mission and its implication to Myanmar context - Zatel, Tomas (Quezon City, Manila : St. Andrew's Theological Seminary, 2009)
Mission is central to theology. Thus to perceive mission in all its multi-dimensions surely helps one to live out his/her Christian faith as a disciple of Christ in a new and challenging situation
There are still some divergences among Christians when it comes to doing mission today. And many Christians and churches in Myanmar are still vague about 'how to go about doing mission' in a religiously pluralistic and political hostile society Myanmar. Thus, to this researcher, there is a need to search for a new way of looking at mission, a more relevant way of engaging mission in the country
Submitted to the faculty of Saint Andrew's Theological Seminary
In partial fulfillment of the requirements for the Degree Master in Divinity